Is prenatal diet associated with the composition of the vaginal microbiome?. Issue 2 (28th November 2021) - Rosen, Emma M.; Martin, Chantel L.; Siega‐Riz, Anna Maria; Dole, Nancy; Basta, Patricia V.; Serrano, Myrna; Fettweis, Jennifer; Wu, Michael; Sun, Shan; Thorp, John M.; Buck, Gregory; Fodor, Anthony A.; et al.
Abstract: Background: The vaginal microbiome has been associated with adverse pregnancy outcomes, but information on the impact of diet on microbiome composition is largely unexamined. Objective: To estimate the association between prenatal diet and vaginal microbiota composition overall and by race. Methods: We leveraged a racially diverse prenatal cohort of North Carolina women enrolled between 1995 and 2001 to conduct this analysis using cross‐sectional data. Women completed food frequency questionnaires about diet in the previous 3 months and foods were categorised into subgroups: fruits, vegetables, nuts/seeds, whole grains, low‐fat dairy, sweetened beverages and red meat. We additionally assessed dietary vitamin D, fibre and yogurt consumption. Stored vaginal swabs collected in mid‐pregnancy were sequenced using 16S taxonomic profiling. Women were categorised into three groups based on predominance of species: Lactobacillus iners, Lactobacillus miscellaneous and Bacterial Vaginosis (BV)‐associated bacteria. Adjusted Poisson models with robust variance estimators were run to assess the risk of being in a specific vagitype compared to the referent. Race‐stratified models (Black/White) were also run. Results: In this study of 634 women, higher consumption of dairy was associated with increased likelihood of membership in the L. crispatus group compared to the L. iners group in a dose‐dependent manner (risk ratio quartile 4 vs. 1: 2.01, 95% confidence interval 1.36, 2.95). Increased intake of fruit, vitamin D, fibre and yogurt was also associated with increased likelihood of membership in L. crispatus compared to L. iners, but only among black women. Statistical heterogeneity was only detected for fibre intake. There were no detected associations between any other food groups or risk of membership in the BV group. Conclusions: Higher consumption of low‐fat dairy was associated with increased likelihood of membership in a beneficial vagitype, potentially driven by probiotics.